Functional adhesion of pectin biopolymers to the lung visceral pleura - Zheng, Yifan; Pierce, Aidan F.; Wagner, Willi Linus; Khalil, Hassan A.; Chen, Zi; Servais, Andrew B.; Ackermann, Maximilian; Mentzer, Steven J. (Polymers, 2021)
Pleural injuries and the associated “air leak” are the most common complications after pulmonary surgery. Air leaks are the primary reason for prolonged chest tube use and increased hospital length of stay. Pectin, a plant-derived heteropolysaccharide, has been shown to be an air-tight sealant of pulmonary air leaks. Here, we investigate the morphologic and mechanical properties of pectin adhesion to the visceral pleural surface of the lung. After the application of high-methoxyl citrus pectin films to the murine lung, we used scanning electron microscopy to demonstrate intimate binding to the lung surface. To quantitatively assess pectin adhesion to the pleural surface, we used a custom adhesion test with force, distance, and time recordings. These assays demonstrated that pectin-glycocalyceal tensile adhesive strength was greater than nanocellulose fiber films or pressure-sensitive adhesives (p < 0.001). Simultaneous videomicroscopy recordings demonstrated that pectin-glycocalyceal adhesion was also stronger than the submesothelial connective tissue as avulsed surface remnants were visualized on the separated pectin films. Finally, pleural abrasion and hyaluronidase enzyme digestion confirmed that pectin binding was dependent on the pleural glycocalyx (p < 0.001). The results indicate that high methoxyl citrus pectin is a promising sealant for the treatment of pleural lung injuries.